Crisis and disasters affecting travelers intention to travel - Kumutha Mauganasondram; Loo Jia Yean; Mohd Fauzul Ibrahim; Noor Akmar Anis Abd Ghani (2016)
This research presents an improved approach to the traveler's intention to travel which are key to increase our understanding towards the barrier to travel. Some crisis and disasters can affect traveler decision and choosing a travel destination. Safety is the important issue for every tourist to go for travel within and abroad country. It can be said safety and security can influence the individual's travelling choice. The importance of this study is to identify the crisis and disasters that affecting traveler's intention to travel. This is a quantitative research conducted in Peninsular Malaysia. The respondents who participated in this research were from north, west and south region. By using SPSS version 23 to analyse the 384 questionnaires from our respondents, we found the crisis and disasters affecting traveler's intention to travel was indicated in four main crisis and disasters which is natural disasters, terrorism, political instability and diseases. The respondents are varying from age, race, gender, region and qualifications. This study found the crisis and disasters like natural disasters, terrorism, political instability and diseases affect traveler's intention to travel. The highest p-value is 0.310 compare with the other variables which is political instability affect the traveler's intention. The limitations of this study and recommendations have been discussed in the last chapters. As a result, the recommendations given in this research study will guide future researchers to carry out the related researches more accurately.